Experimental and numerical investigation on the complex behaviour of the localised seismic response in a multi-storey plan-asymmetric structure - Alam, Zeshan; Sun, Li; Zhang, Chunwei; Su, Zhongxin; Samali, Bijan (Structure and infrastructure engineering, 2021)
Asymmetric structures experience higher seismic damage compared with their symmetric counterparts. This damage is mainly attributed to the coupled torsional vibrations, which tend to induce twisting in the structural floors and increase the shear demands in the corner column of the flexible side (CCFE) of asymmetric structures with in-plan stiffness eccentricity. Such floor twisting consequently leads towards the damage concentration in the critical region of CCFE and produce relatively higher local deformations and stiffness degradation of the structural component. Therefore, the investigation of such damage concentration is important as it can potentially lead towards local and global seismic failure. In this regard, this research aims at evaluating the damage behaviour of CCFE of a plan-asymmetric reinforced concrete (RC) structure. For this purpose, a quarter scaled asymmetric structure with in-plan stiffness eccentricity was experimentally tested under progressive seismic excitations. Internal seismic damage in the critical region of CCFE was monitored using Fibre Bragg grating (FBG) sensors during the structure's transformation from elastic state to a highly plastic state. To validate the experimental findings, a calibrated finite element model was established in ABAQUS and a comparison of the damage behaviour of CCFE is presented to highlight the influence of stiffness eccentricity on damage concentration in the critical structural element. Finally, based on the experimental and numerical investigations, the mechanism of the local response behaviour both at the flexible and stiff edge of the plan-asymmetric structure is discussed and compared. This research concludes that CCFE in plan-asymmetric structures requires substantial design redundancy and special seismic detailing to resist extreme seismic events.